Pengaruh Kedalaman Anestesi Umum terhadap Pemulihan Pasca Bedah Laparotomi: Systematic Literature Review - Cicilia Dwi Diandra; Made Suandika; Fauziah Hanum (Jurnal Anestesi, 2026)
The depth of general anesthesia is an important factor affecting postoperative recovery. Inadequate anesthesia monitoring may increase the risk of delayed recovery, cognitive impairment, delirium, and other postoperative complications. This study aimed to determine the effect of general anesthesia depth on postoperative recovery in patients undergoing laparotomy and laparoscopy procedures. The study used a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Literature was collected from PubMed, ScienceDirect, and Google Scholar covering publications from 2015–2025. Included studies consisted of randomized controlled trials, cohort studies, and retrospective studies discussing the relationship between anesthesia depth and postoperative recovery. Study quality was assessed using the Joanna Briggs Institute (JBI) instrument. A total of 10 studies met the inclusion criteria. The results showed that Bispectral Index (BIS) was the most widely used monitoring method. Recovery outcomes analyzed included quality of recovery, awakening time, extubation time, PACU stay duration, postoperative pain, analgesic requirements, delirium, postoperative cognitive dysfunction (POCD), sleep quality, and other complications. BIS-based monitoring was associated with better early recovery, faster awakening and extubation, and reduced short-term cognitive impairment. Therefore, the depth of general anesthesia significantly influences postoperative recovery quality.